Successful regression of newly formed corneal neovascularization by subconjunctival injection of bevacizumab in patients with chemical burns - Peng, Wen-yan; He, Li-wen; Yin, Xiao-fang; Zhou, Bin-Bing; Zhou, Tao; Zhou, Shi-you (Frontiers in medicine, 2023)
To investigate the effect and timing of subconjunctival bevacizumab injection on inhibiting corneal neovascularization (CorNV) in patients after chemical burns. Patients with CorNV secondary to chemical burns were involved. Two subconjunctival injections of bevacizumab (2.5 mg/0.1 mL per involved quadrant) with an interval of 4 weeks were administered, and followed up a year. The area occupied by neovascular vessels (NA), accumulative neovascular length (NL), mean neovascular diameter (ND), best-corrected visual acuity (BCVA) and intraocular pressure (IOP) were evaluated. Complication was also recorded. Eleven patients with CorNV were involved. Eight patients had a history of surgery (four had amniotic grafts, one had keratoplasty, and three had amniotic grafts and keratoplasty). Decreasing in NA, NL, and ND were statistically significant at each time point compared to the baseline ( 0.01). CorNV that developed within 1 month was considerably regressed, and vessels with fibrovascular membranes were found to be narrower and shorter than pretreatment. BCVA improved in five patients (from one to five lines), remained unchanged in five patients, and decreased in one patient compared to pretreatment. Subconjunctival bevacizumab injection has a particular potential for the regression of CorNV, especially newly formed within 1 month in patients after chemical burns.